(untitled) (Research, Society and Development, 2020)
The present bibliometric study aims to analyze the scientific production on the theme Organizational Links, in the Web of Science and Scopus databases (CAPES, 2020). As a research method, bibliometric analysis with a quantitative and descriptive approach was used. It was a survey of publications in the period from 2008 to 2019, the data were collected on the Web of Science and Scopus, using as keyword "organizational links". The analysis considered the following elements: time evolution, total number of publications, thematic area, type of document, countries, main authors and citation report. As a method for data analysis, the VOSviewer system was used to create textual maps, co-citation clusters and keywords. The survey results show that the topic is relevant, particularly in the period 2008-2019, in the area of business, management and accounting. In addition, the bibliometric study allows researchers to be able to develop and expand knowledge in this field of study. As a limitation of the study, the realization in only one database stands out, it is suggested that future studies expand the sample to include national and international academic events, academic journals, as well as other scientific databases. In relation to practical implications, the use of bibliometrics, contributes to measure the indexes of production and dissemination of scientific knowledge and to disseminate knowledge.